Use of waste plastic aggregation in concrete as a constituent material (Progressive Agriculture, 2016)
The amount of Plastics consumed annually has been growing increasingly in Bangladesh. Consequently, waste plastic recycling has become one of the major challenges in recent times. The present study has selected waste PET, a polymer compound of Polyethylene Terephthalate, to investigate its possible use as plastic aggregate in concrete application. The shredded waste plastic was used in concrete with partial replacement of 5%, 10% and 20% by volume of conventional coarse aggregate. Four types of concrete specimens including one without plastic aggregate, for comparison purpose, were prepared. All the concrete specimens were tested for its different mechanical properties after a curing period of 7, 21 and 28 days. Various physical properties of all aggregates and fresh concrete properties were also tested in the laboratory. The specific gravity of waste plastic aggregate was found 1.4 and the maximum density of concrete containing plastic aggregate was 115 lb/ft3. The density of concrete specimens containing plastic aggregate decreased with the addition of more amount of plastic aggregate. It was found that the concrete specimen containing waste PET at 10% volume showed higher compressive strength and higher modulus of elasticity than other specimens. The splitting tensile strength was about 8-11% of compressive strength. The flexural strength of concrete specimens containing plastic aggregate was lower than that of concrete without plastic aggregate. It was found that the strength of concrete containing PET aggregate falls in the category of lightweight concrete in terms of their strength, specific gravity and density. Thus, the waste PET aggregate could be effectively used to reduce the unit weight of concrete which results in a reduction in the dead weight of a structural concrete. Furthermore, it is concluded that the use of waste PET in concrete provides some advantages such as  reduction in the use of conventional aggregate, disposal of wastes, prevention of environmental pollution, and energy saving.Progressive Agriculture 27 (3): 383-391, 2016